Police Reform, Civil Society and Everyday Legitimacy: A Lesson From Northern Ireland - Marijan, Branka; Guzina, Dejan (Journal of Regional Security, 2018)
In post-conflict zones, there is a need to better understand the role of civil society in building the legitimacy of reformed police institutions. Northern Ireland provides an instructive case in this regard, as community involvement and civilian oversight of policing structures were prominent in the reform process. While much has been achieved since the 1999 Independent Commission on Policing, the question of police legitimation is still largely unresolved. In order for police reform to be fully realized, and to ensure that everyday legitimacy is established, more attention must be paid to building relationships between the police and local communities.